Approach to vaccinating the pediatric solid organ transplant candidate and recipient - Kao, Carol M.; Michaels, Marian G. (Frontiers in Pediatrics, 2023)
Solid organ transplantation (SOT) candidates and recipients are at increased risk for morbidity and mortality from vaccine-preventable infections. Children are at particular risk given that they may not have completed their primary immunization series at time of transplant or have acquired natural immunity to pathogens from community exposures. Multiple society guidelines exist for vaccination of SOT candidate and recipients, although challenges remain given limited safety and efficacy data available for pediatric SOT recipients, particularly for live-vaccines. After transplant, individual patient nuances regarding exposure risks and net state of immunosuppression will impact timing of immunizations. The purpose of this review is to provide readers with a concise, practical, expertopinion on the approach to vaccinating the SOT candidate and recipient and to supplement existing guidelines. In addition, pediatric-specific knowledge gaps in the field and future research priorities will be highlighted.